Syncope, the “Forgotten-Sign” of a Life-Threatening Pulmonary Embolism - Sylvia Alicia Salim; Christine Anita (Eduvest - Journal of Universal Studies, 2026)
Pulmonary embolism (PE) is one of the most common forms of venous thromboembolism (VTE), with a relatively high annual incidence of approximately 39–115 per 100,000 population. Given its widely variable clinical presentations, PE can be life-threatening if not recognized and treated early. Syncope is a relatively common and clinically important presentation of PE; however, in daily practice, it is often not immediately considered in the differential diagnosis. We reported a case of a 37-year-old male who complained of sudden blackout and a sensation of near-fainting, with a history of shortness of breath following mild daily activities, which was later diagnosed as PE with a D-dimer level of >10 µg/mL. The addition of fondaparinux to his treatment regimen significantly improved his condition. The prognosis of patients depends on the underlying pathology, patient risk factors, duration from symptom onset to hospital admission, and the use of thrombolytic agents. This case report was prepared to increase clinicians’ awareness of PE as a potential cause of syncope, in order to prevent life-threatening complications.